Enhancing the Encryption Capabilities of the Generalization of the ElGamal Algorithm for Document Security - Zega, Imanuel; Yulianto, Bagas Dwi (Journal of Applied Informatics and Computing, 2025)
The development of cryptographic algorithms that are efficient in terms of computation and resource usage, in addition to maintaining the confidentiality, integrity, and authentication of information, is driven by the growing need for digital document security. The generalization of the ElGamal, an expansion of the traditional ElGamal algorithm with more adaptable encryption features, is one algorithm with a lot of promise in this situation. The implementation of the technique of splitting the plaintext into three-digit blocks to lower the complexity of encryption per character and the use of large prime numbers to increase the algorithm's mathematical complexity are the two main ways that this study seeks to increase the algorithm's efficiency and security. It is anticipated that this method will speed up computation time and simplify the encryption process per character without compromising security. The overall findings demonstrate that, without compromising security, this method dramatically cuts down on computation time and ciphertext enlargement. Therefore, in the age of digital transformation, the findings of this study aid in the creation of contemporary cryptographic algorithms that are more flexible and effective and serve as a strategic guide when creating a strong digital data security system.